Analyze the writing skills among the students of the private religious school - Ismail, Noor Hidayah; Md Sabil, Azhar; Othman, Shamsudin; Said, Rozita @ Radhiah (Human Resource Management Academic Research Society, 2017)
The purpose is to analyze the writing skills among the students of the private religious school. Students' writing skills are very weak as their study syllabus focuses on the subject of Diniiyah. In this study, the Master should first be prepared with the knowledge and skills of the discourse in writing skills in order to channel the knowledge properly to the pupils despite the time constraints during the R & D process. This paper is important to illustrate how important it is to master the writing in accordance with the principles of correct discourse in order to preserve Malay language apart from helping students to excel in the examination.